THE CENOZOIC EVOLUTION OF THE STRONTIUM AND CARBON CYCLES: RELATIVE IMPORTANCE OF CONTINENTAL EROSION AND MANTLE EXCHANGES - Godderis Y.; Francois L.M. (My University, 1995)
The past variations of the seawater 87Sr86Sr isotopic ratio are related to changes in the relative contribution of the mantle Sr input to the ocean and the Sr supply from continental weathering. Recently, it has been postulated that the Cenozoic increase in the seawater 87Sr86Sr isotopic ratio was associated with the uplift of the Himalayan and Andean mountains at that time. These orogenies may have changed the Sr isotopic ratio of the continental rocks undergoing weathering (as a result of extensive metamorphism), increased the river flux of Sr through enhanced weathering in these regions and possibly caused the global climatic cooling trend of the Cenozoic. A model of the major geochemical cycles coupled to an energy balance climate model is used to explore the possible causes of the Mesozoic-Cenozoic fluctuations in the seawater 87Sr86Sr isotopic ratio. The contribution of the mantle exchanges at mid-ocean ridges, of the recycling of seafloor carbonates through plate margin volcanism and of the alteration of seafloor basalts to the fluctuations of the seawater 87Sr86Sr isotopic ratio are studied. Finally, this model tentatively describes the impact of the Himalayan orogeny on the geochemical cycles of Sr and C. Some possible effects of the extensive metamorphism associated with the India-Asia collision and of the Himalayan uplift are modelled. The model reproduces the Cenozoic increase of the seawater 87Sr86Sr isotopic ratio. However, the impact of the Himalayan orogeny on the C cycle appears to be limited and insufficient to generate the global climatic cooling of the Cenozoic. Rather, in the model, the Cenozoic cooling is mostly due to the reduction of the CO2 emission from mid-ocean ridge volcanism and to changes in the chemical weathering rates in the rest of the world excluding the Himalayas.
Keywords: Cenozoic; Cenozoic; Кайнозой